American Revolution : the definitive encyclopedia and document collection - Tucker, Spencer, 1937-; Arnold, James R., 1952-; Wiener, Roberta, 1952-; Pierpaoli, Paul G., Jr., 1962-; Nelson, Paul David, 1941-; Piecuch, Jim; Black, Jeremy, 1955- (ABC-CLIO, an imprint of ABC-CLIO, LLC, 2018)
This definitive scholarly reference covers the causes, course, and consequences of the war and the political, social, and military origins of the nation. It covers not only the eight years of the American Revolutionary War (1775-1783) but also the decades leading up to the war, beginning with the French and Indian War, and the aftermath of the conflict, with an emphasis on the early American Republic.